Diversidad y almacenamiento de carbono del arbolado urbano en la ciudad de Loja, Ecuador - Merino Galvez, Bryan Javier (2024)
Urban trees provide a number of environmental, social and economic benefits; however, current knowledge about urban trees in Ecuador is limited. The objective of this research was to contribute to the knowledge of tree diversity and carbon storage of urban trees in the city of Loja, Ecuador. The database of the forest inventory of the parks and avenues of the urban area of the city of Loja generated in the project: Dynamics of growth and ecosystem services of urban trees in the city of Loja was used. For the floristic and structural characterization, individuals ≥ 5 cm DAP were considered. Taxonomic diversity and specific richness were calculated, and for the structure, the following parameters were analyzed: abundance, specific dominance, equitability and biogeographic origin (native and exotic). Diversity was assessed using the Margalef (DMg); Simpson (δ); Berger - Parker (d) and Shannon (h') indices. The indices were calculated separately in parks (Recinto Ambiental Urbano, RAU) and avenues (Vecindario Verde Inclusivo, VVI). Estimation of aboveground biomass storage was performed using allometric equations available in the literature, and the fraction of 0,47 suggested by IPCC was used to obtain carbon accumulation. A total of 5,259 individuals were recorded, of which 5,084 were trees, 27 shrubs and 148 palms, belonging to 91 species, 67 genera and 35 botanical families. The botanical families with the greatest diversity in genera were Fabaceae with 17 species representing 18,7%, Myrtaceae with 11 representing 12,1%, Bignoniaceae, Moraceae, Rosaceae with five representing 5.5% and Arecaceae with three representing 3,3%. The species with the highest abundance in parks and avenues were Salix humboldtiana, Jacaranda mimosifolia, Alnus acuminata and Vachellia macracantha. The Margalef diversity index was 9,95 and 6,66; Simpson's index of 0,93 and 0,89; Berger-Parker of 0,19 and 0,25; Shannon's index of 2,57 and 2,54, representing a fairness, especially in the Urban Environmental Precinct, RAU, where diversity was high, and in the Inclusive Green Neighborhood, VVI, a medium diversity. The total amount of carbon stored in urban trees in the city of Loja was 1,963.49 tC, the exotic species stored more carbon with 76,18% as opposed to the native species with 23,82 %. The species that registered the highest amount of carbon stored were Salix humboldtiana, Cupressus macrocarpa, Schinus molle and Jacaranda mimosifolia.